Identifikasi Ikonologi Musik Yogyakarta Royal Orchestra Melalui Perspektif Pariwisata dan Budaya - Rahafuna, Muhammad Zumar; Hakim, Lutfi Maulana; Kusumastiti, Weka (Mahesa Research Center, 2025)
This article aims to identify the music iconology of the Yogyakarta Royal Orchestra's (YRO) through a tourism and cultural perspective. The problem focuses on the unidentified aspects of the YRO that could become musical icons that can be developed as tourist attractions based on a cultural perspective. To approach this problem, theoretical references from (Falvy 1977) related to musical iconology and its analysis and interpretation (Buckey, 1998) are used. The main data are interviews with key actors of the YRO and visitors to the show. The results of the interviews were analyzed qualitatively using triangulation methods to ensure the credibility of the results. The results indicate that the YRO has iconological potential and can become a musical tourism icon of the Yogyakarta Palace in the form of something that can be perceived by the senses (audio and visual) because it contains and represents the culture of the Yogyakarta Palace. This is because tourists are generally only able to capture audio-visual messages, not yet reaching the stage of meaning. Further holistic research is needed regarding the tourism aspects of the YRO in an effort to form a scientific framework for the related topic.